Critical rationality from a cross-cultural perspective - David F. Hemphill (Adult Education Research Conference, 1994)
This paper explores the impacts of cultural transition on the adult cognitive process of critical rationality. It presents ethnographic findings from case studies of Asian immigrants who successfully negotiate the cultural transition to work positions of supervisory responsibility. A series of findings--some culture-specific, some broader--are reported. Finally, a critique of the study's conception of the presumed universality of critical rationality is offered from a postmodernist, cross-cultural perspective, suggesting that prevailing conceptions of critical rationality may be culturally bound, thus requiring re-examination. This paper is presented in two parts: the first reports on a study of critical rationality among Chinese immigrant adults in the United States; the second reflects on the underlying conceptual framework of the study, calling into question the notion of critical rationality employed in the study as an unexamined, arguably Eurocentric thought form that needs to be recast in the context of a multicultural society.